Biopsy. - García Giesmann, J. (2015)
Biopsy means study "in vivo",. But use the term identified with taking a sample of tissue for study or fragment thereof The purpose of a biopsy, is used in a patient with a tumor or any another form of disease, histological data obtained on the nature of disease.